(untitled) (Journal of the Association for the Study of Australian Literature, 2007)
In both her fiction and autobiographical essays, author Lily Brett describes the process of travelling ‘home’ to Poland as an adult child of Holocaust survivors. In a close reading of her novel Too Many Men, I will discuss the contemporary concern with returning to the ‘past’ for a sense of contemporary ‘self’ represented in this novel. In Too Many Men the protagonist Ruth journeys to Poland with her father, visiting the sites of his former life and the places of his family’s destruction. However, the journey represents very different things for these two characters. Sites of memory, ‘simulation’ and the ‘trace’ are key ideas adopted in this reading.